The Correlation Between Syndecan-1 Post Cardiopulmonary Bypass and Duration of Ventilator Use in Open Heart Surgery Patients at Dr. Sardjito General Hospital, Yogyakarta - Fatmi Eka Putri; Synthana, Meta Restu; Kurniawaty, Juni (Jurnal Komplikasi Anestesi, 2026)
Background: Open heart surgery involves the use of a cardiopulmonary bypass machine (CBP) to replace the heart and lungs during surgery. The use of CBP can damage the endothelial glycocalyx, which triggers increased levels of syndecan-1, an indicator of endothelial degradation. Elevated syndecan-1 levels are associated with various complications, such as coagulation disorders, edema, and organ dysfunction. In the lungs, endothelial glycocalyx damage can lead to edema and lung parenchymal damage, which can impair overall lung function and lead to a decreased PaO2/FiO2 ratio, requiring prolonged postoperative ventilator use.Objective: This study aimed to determine the relationship between post-CBP syndecan-1 levels and the duration of ventilator use in open heart surgery patients at Dr. Sardjito General Hospital, Yogyakarta.Methods: This study was a prospective, analytical, observational cohort study conducted at Dr. Sardjito General Hospital, Yogyakarta. The sample consisted of adult patients undergoing open heart surgery, with the exclusion criteria being patients using preoperative mechanical assist devices. Syndecan-1 levels were measured using the ELISA method using the Elabscience Human SDC1 kit. Data were analyzed using SPSS. Bivariate and multivariate analyses were also performed to evaluate factors influencing ventilator duration.Results: The study was conducted on 34 subjects with a mean age of 46 ± 13.71 years. The average CPB duration was 92.94 ± 47.57 minutes, with preoperative syndecan-1 levels of 8.86 ± 5.08 ng/ml, while post-CPB levels were 11.74 ± 3.71 ng/ml, with delta syndecan-1 levels of 2.87 ± 4.18 ng/ml.